Early Intervention and Parent Counseling Give Positive Impact in Cerebral Palsy Child: A Case Report - Sultana, Selina; Wahab, Abdul; Chowdhury, Rajib Nayan; Sultana, Marin; Salam, Abdus (Bangladesh Journal of Medical Science, 2022)
Cerebral palsy is a neuro-development disorder, management of which requires awareness of risk factors and regular developmental assessments. Committed routine follow up is necessary for cerebral palsy patient along with parental adequate knowledge.Effective timely intervention with professional guidance along with medication could significantly improve the overall condition of cerebral palsy patient and therefore would make their living relatively meaningful.Early intervention starts withinfirst 6 months after term age. Intervention should be performed daily in home consideringthe importance of parent child relationship, training and counseling by professionalguidance. In fact, Parental knowledge of their child’s cerebral palsy is inadequate. If professionals give early intervention to the child and improve parental knowledge about cerebral palsy will empower them to help their children to overcome this chronic lifelong disorder. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 926-930